KINETIC SOLUBILITY OF MEBENDAZOLE NANOCRYSTAL - Dzakwan, Muhammad (Jurnal Kesehatan Bakti Tunas Husada: Jurnal Ilmu-ilmu Keperawatan, Analis Kesehatan dan Farmasi, 2018)
MBZ nanosuspensions were produced by high pressure homogenization and transformed into dry powder by lyophilization. MBZ nanocrystals were intensively evaluated regarding their physicochemical properties with respect to particle size analyses, crystallinity and kinetic solubility. The particle size was determined by photon correlation spectroscopy (PCS. DSC and X-ray diffraction were used to study the crystalline state of MBZ nanocrystals. In a period of 1 week, the kinetic solubility was determined using a shaker water bath at 37O C. DSC and X-ray diffraction analyses showed that lyophilized MBZ nanocrystals prepared by high pressure homogenization remained in crystalline state. Lyophilized MBZ nanocrystals could be re-dispersed completely in water and the kinetic solubility in water increased 9 fold, from 60,57 ηg/ml to 598 ηg/ml